Ejection fraction-related differences of baseline characteristics and outcomes in troponin-positive patients without obstructive coronary artery disease - Kaçmaz, Mustafa; Schlettert, Clara; Kreimer, Fabienne; Abumayyaleh, Mohammad S. A.; Akın, Ibrahim; Mügge, Andreas; Aweimer, Assem; Hamdani, Nazha; El-Battrawy, Ibrahim (Journal of Clinical Medicine, 2024)
Background: The development and course of myocardial infarction with non-obstructive coronary artery (MINOCA) disease is still not fully understood. In this study, we aimed to examine the baseline characteristics of in-hospital outcomes and long-term outcomes of a cohort of troponin-positive patients without obstructive coronary artery disease based on different left ventricular ejection fractions (LVEFs). Methods and results: We included a cohort of 254 patients (mean age: 64 (50.8-75.3) years, 120 females) with suspected myocardial infarction and no obstructive coronary artery disease (MINOCA) in our institutional database between 2010 and 2021. Among these patients, 170 had LVEF ≥ 50% (84 females, 49.4%), 31 patients had LVEF 40-49% (15 females, 48.4%), and 53 patients had LVEF < 40% (20 females, 37.7%). The mean age in the LVEF ≥ 50% group was 61.5 (48-73) years, in the LVEF 40-49% group was 67 (57-78) years, and in the LVEF < 40% group was 68 (56-75.5) years (p = 0.05). The mean troponin value was highest in the LVEF < 40% group, at 3.8 (1.7-4.6) µg/L, and lowest in the LVEF ≥ 50% group, at 1.1 (0.5-2.1) µg/L (p = 0.05). Creatine Phosphokinase (CK) levels were highest in the LVEF ≥ 50% group (156 (89.5-256)) and lowest in the LVEF 40-49% group (127 (73-256)) (p < 0.05), while the mean BNP value was lowest in the LVEF ≥ 50% group (98 (48-278) pg/mL) and highest in the <40% group (793 (238.3-2247.5) pg/mL) (p = 0.001). Adverse in-hospital cardiovascular events were highest in the LVEF < 40% group compared to the LVEF 40-49% group and the LVEF ≥ 50% group (56% vs. 55% vs. 27%; p < 0.001). Over a follow-up period of 6.2 ± 3.1 years, the all-cause mortality was higher in the LVEF < 40% group compared to the LVEF 40-49% group and the LVEF ≥ 50% group. Among the different factors, LVEF < 40% and LVEF 40-49% were associated with an increased risk of in-hospital cardiovascular events in the multivariable Cox regression analysis. Conclusions: LVEF has different impacts on in-hospital cardiovascular events in this cohort. Furthermore, LVEF influences long-term all-cause mortality.
Gesehen am 12.12.2024